Response of microbial adhesives and biofilm matrix polymers to chemical treatments as determined by interference reflection microscopy and light section microscopy. - Marshall, P A (1989)
The polymers involved in the adhesion of Pseudomonas fluorescens H2S to solid surfaces were investigated to determine whether differences between cell surface adhesives and biofilm matrix polymers could be detected. Two optical techniques, i.e., interference reflection microscopy (IRM) and light section microscopy (LSM), were used to compare the responses of the two types of polymer to treatment with electrolytes, dimethyl sulfoxide (DMSO), and Tween 20. To evaluate initial adhesive polymers, P. fluorescens H2S cells were allowed to attach to glass cover slip surfaces and were immediately examined with IRM, and their response to chemical solutions was tested. With IRM, changes in cell-substratum separation distance between 0 and ca. 100 nm are detectable as changes in relative light intensity of the image; a contraction of the polymer would be detected as a darkening of the image, whereas expansion would appear as image brightening. To evaluate the intercellular polymer matrix in biofilms, 3-day-old biofilms were exposed to similar solutions, and the resultant change in biofilm thickness was measured with LSM, which measures film thicknesses between 10 and 1,000 microns. The initial adhesive and biofilm polymers were similar in that both appeared to contract when treated with electrolytes and to expand when treated with Tween 20. However, with DMSO treatment, the initial adhesive polymer appeared to contract, whereas there was no change in thickness of the biofilm polymer. These results indicate that both polymers bear acidic groups and thus act electrostatically with cations and are able to enter into hydrophobic interactions.(ABSTRACT TRUNCATED AT 250 WORDS)